Epigenetic silencing of EphA1 expression in colorectal cancer is correlated with poor survival - Herath, N I (Nature Publishing Group, 2009)
Aberrant expression of Eph and ephrin proteins has well-established functions in oncogenesis and tumour progression. We describe EphA1 expression in 6 colorectal cancer (CRC) cell lines, 18 controls and 125 CRC specimens. In addition, a well-characterised cohort of 53 paired normal colon and CRCs was also assessed. Expression of EphA1 mRNA was assessed by quantitative real-time PCR and correlated with protein expression by flow cytometry, immunoprecipitation, western blotting and immunohistochemistry. Significant upregulation (2- to 10-fold) of EphA1 was seen in over 50% of cases (P=0.005) whereas many of the remainder showed downregulation of EphA1. Intriguingly, EphA1 over-expression was more prevalent in stage II compared to stage III CRCs (P=0.02). Low EphA1 expression significantly correlated with poor survival (P=0.02). Epigenetic silencing appeared to explain the loss of EphA1 expression as methylation of the EphA1 CpG island strongly correlated with low EphA1 expression (P<0.01). Furthermore, EphA1 re-expression could be induced by treatment with demethylating agents. Our findings identify EphA1 as a potential prognostic marker in CRC. Although therapies targeting high EphA1 expression seem plausible in CRC, the loss of expression in advanced disease suggests a potential risk that targeted therapy, by selecting for loss of expression, might contribute to disease progression.